PERANCANGAN KENDALI SUPERVISI PADA SISTEM EVEN DISKRIT - Wahjudi, Rudy S (Jurnal Teknik Elektro, 2005)
In Scheme Of Control System Supervise The, Knowledge Hit In Control System Play RoleVery Important. Scheme Problem Become Complicated Progressively If Supervision Of ResultOf Design Of Specification Base Of System Wanted By Designer Cannot Prevent TheUndesirable Process. Solution For The Matter Of Like This Claim The Knowledge Hit InControl System And Specification Of System Wanted In More Circumstantial. In This PaperWill Study The Method Development In Control System Through Development OfSpecification Of System, So That The Specification Of System Reached By Paying Attention ToSystem Security. The Development Of Controllability System Method Through DevelopmentOf Specification Of The System Later Then Application To Design The SupermarketSupervisionKeywords: Controllability System, Supervise, Extended Controllable System